Analisis Penerapan Metode Fifo (First In First Out) Dan Fefo (First Expired First Out) Pada Food & Beverage Store Prama Sanur Beach Bali - I Made Sastrawan Adnyana Putra (UNHI Press, 2026)
This study aims to analyze the inventory management process and the impact of implementing the First Expired First Out (FEFO) method in the management of Food and Beverage inventory at Prama Sanur Beach Bali Hotel. Effective inventory management is essential in the hospitality industry, particularly for food and beverage materials that have a limited shelf life. Previously, the hotel applied the First In First Out (FIFO) method, which releases goods based on the order of their arrival without considering expiration dates. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research informants consist of the receiving department, warehouse staff, and kitchen staff who are directly involved in inventory management. The results show that the implementation of the FEFO method has a positive impact on inventory management by improving control over expiration dates, maintaining the quality of raw materials, and reducing the risk of spoilage and food waste. Therefore, the FEFO method is considered more effective than the FIFO method in managing Food and Beverage inventory at Prama Sanur Beach Bali Hotel.